PERAN GURU DALAM MENANAMKAN KARAKTER PERCAYA DIRI PADA PEMBELAJARAN TEMATIK BERBASIS DARING - Eka Putri Martiyana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to determine the teachers’ role in building confidence character in online based thematic learning at SDIT Al-Izzah, Serang Banten at grade IV Salman. This research used descriptive qualitative. The data were collected through interviews, observations, and documentation. This research had sub focus of: 1) how is the teachers’ plan before implementing learning activities in building the character of confidence? 2) how is the students’ self-confidence built through online-based thematic learning? 3) how is the character of the students’ self confidence through online-based thematic learning process? Based on the result of the study, it could be seen that the teacher designed a lesson plan in which the teacher used the method and audio visual media to explain the material. Then, the teachers communicated with the students’ parents by using WhatsApp and Video call applications and finally, the teachers designed the learning evaluations. In addition, to build the character of confidence during the thematic learning process, the teacher began the learning activities by greeting students and giving encouragement. Then, it was continued with the core activities in which the teachers recalled the students’ knowledge, stimulated students’ participation by conducting a question-and-answer session personally, and evaluated the students’ understanding by asking some questions on google form/online quiz. As the closing activity, the teachers gave assignments in the form of dancing practice, assignments or writing tests and daily journals. Related to the character of confidence, after going through an online thematic learning, it was seen that the students did not hesitate to ask questions; they were more enthusiastic about doing assignments given by the teacher and were confident enough to collect answers to practice questions and to send dance practice videos or create communication media.